The value of photovoice in researching the 2012 Marikana massacre - Langa, Malose; Merafe, Modiegi; Rebello, Steven (PINS-Psychology in Society, 2022)
Following the 2012 massacre in Marikana, the Centre for the Study of Violence and Reconciliation (CSVR) trained a group of community members on basic trauma counselling skills, as a means of providing emotional support to the victims and their families. In an evaluative study, eight members of the support group were provided with disposable cameras and asked to take pictures under the theme ‘life in Marikana pre and post the 2012 massacre’. Arrangements were made for photos to be collected and processed. In total, 98 photos were processed. A focus group meeting was held with group members, to go through their photos and discuss what these photos represented. Each group member was given an opportunity to share the story about each photo taken. The focus group meeting in this study allowed participants to share their own insights and to build upon responses of other group members, thus enriching the process of data collection and allowing the participants to share their lived experiences in Marikana. The photo-narrative method proved as a useful research tool in highlighting participants’ frustration and consciousness of their prolonged poor living conditions, and exploitation, given the vast wealth of the Lonmin platinum mines. The method also proved useful in providing a space for participants to discuss how their community could possibly heal from the massacre of 2012, with continued tensions, divisions and empty promises greatly undermining healing. It is concluded in this article that photovoice is one of the effective research tools in qualitative research design to allow community members to explicitly, through visuals taken, discuss issues affecting them daily.